Characterization of Ethanol Extract from Katumpangan Air Herbs (Peperomia pellucida L. Kunth - Angelina, Marissa; Amelia, Puteri; Irsyad, Muchammad; Meilawati, Lia; Hanafi, Muhammad (Balai Riset dan Standardisasi Industri Pontianak, 2015)
Peperomia pellucida L. Kunth known as âKatumpangan Airâ is a potential medicinal plants used traditionally for uric acid, rheumatic, headache, stomachache, antimicrobial. This study aims to establishÂ the non-specificÂ and specific parameters of ethanol extract from Katumpangan air (EKA). EKA was collected from three different growth places: South Tangerang (6.833%), Bogor (7.8%) and Yogyakarta (13.125%). The results show that organoleptic extract characterization from three places were same: thick, blackish green brown, bitter and have a characteristic odor. The average content of water-soluble compounds was within range 7.39-13.29%, ethanol-soluble 15.33-16.68%, flavonoid total 3.807-4.244%. The range of moisture content was 12.25-16.34%, ash total 1.21-2.78%, acid insoluble ash 0.19-1.62%, drying shrinkage 21.62-24.98%, specific gravity 1.0010-1.0034 g/mL for the non-specific parameter. Microbial contamination testing results 0.61x103-1.13x103 coloni/g, the contaminant testing mold/yeast 0.1x102-1.7x102 coloni/g, while lead metal 0.15-0.18 mg/kg, cadmium 0-0.11 mg/kg and arsenic <0.005Âµg/kg.